Association between Asthma and Risk of Developing Obstructive Sleep Apnea - Teodorescu, Mihaela (JAMA, 2015)
IMPORTANCE: Obstructive sleep apnea (OSA) is more common among patients with asthma; whether asthma is associated with the development of OSA is unknown. OBJECTIVE: To examine the prospective relationship of asthma with incident OSA. DESIGN: Population-based prospective epidemiology study (the Wisconsin Sleep Cohort). SETTING: Beginning in 1988, adult participants were recruited from a random sample of Wisconsin state employees to attend overnight polysomnography studies at 4-year intervals. Asthma and covariate information were assessed during polysomnography studies through March 2013. PARTICIPANTS: Participants identified as free of OSA (apnea-hypopnea index<5 events/hr and not treated) by two baseline polysomnography studies and that had at least one additional polysomnography study were included. 547 participants (52% women; mean [SD] baseline age = 50 [8] years) provided 1105 4-year follow-up intervals. EXPOSURE: Questionnaire-assessed presence and duration of self-reported physician-diagnosed asthma. MAIN OUTCOME: The associations of presence and duration of asthma with 4-year incidences of both OSA (apnea-hypopnea index ≥ 5 or positive airway pressure treatment) and OSA concomitant with habitual daytime sleepiness were estimated using repeated-measures Poisson regression, adjusting for confounders. RESULTS: Twenty-two out of 81 (27% [95% CI=17%–37%]) participants with asthma experienced incident OSA over their first observed 4-year follow-up interval compared to 75 incident cases of OSA among 466 participants without asthma (16% [95% CI, 13%–19%]). Using all 4-year intervals, participants with asthma experienced 45 incident OSA cases during 167 4-year intervals (27% [95% CI, 20%–34%]) and participants without asthma experienced 160 incident OSA cases during 938 4-year intervals (17% [95% CI, 15%–19%]); the corresponding adjusted relative risk was 1.39 (95% CI, 1.06–1.82), controlling for sex, age, baseline and change in body mass index, and other factors. Asthma was also associated with new-onset OSA with habitual sleepiness (relative risk: 2.72 [95% CI, 1.26–5.89], p=0.04). Asthma duration was related to both incident OSA (relative risk: 1.07 per 5-year increment in asthma duration [95% CI, 1.02–1.13], p=0.01) and incident OSA with habitual sleepiness (relative risk: 1.18 [95% CI, 1.07–1.31], p=0.02). CONCLUSIONS AND RELEVANCE: Asthma was associated with increased risk of new-onset OSA. Studies investigating the value of periodic OSA evaluation in patients with asthma are warranted.